Evaluating the Effects of Information Literacy on Climate Change Awareness among Students in Imo State University - N. Patricia Duru; C. Faisal Emetumah (Archives of Current Research International, 2016)
The 21st century ushered in the information age which in alignment with technology, has made access to information easier and faster than the world has ever seen. However, information is only beneficial when its articulate form is appropriately directed at those that need it the most; that is what information literacy is all about. The reality of climate change and its impact on our everyday lives point to the pertinence of having lucid information which will in turn create more awareness on climate change. Reviewed literatures suggest that even though a lot of information is available on climate change issues, there are still significant gaps in the perception of the concept by many segments of human society, particularly in the developing world. The aim of the study is to determine how information literacy affects awareness on climate change issues among students in Imo state university. Survey method involving questionnaires was used in gathering primary data from a study population of 20,000 undergraduate students, from which samples of 392 respondents were purposively and randomly selected. Analysis of the study results produced vital findings: 37.8% of the respondents get information on climate change issues mostly from the internet which was also seen by 53.6% of the respondents as the most accessible information source. While about 60% of the respondents both strongly agreed and agreed that climate change positively affects Nigeria’s economy, 35% did not have any opinion on whether or not climate change aggravates expanding deserts worldwide. The study concludes that though technology and the internet are very important in sourcing information on climate change issues, the quality and the ability of the respondents to understand that information is subjective. The study recommends more awareness creation on climate change issues through public participation and technological tools.